X-ray groups and clusters of galaxies in the Subaru-XMM Deep Field - Finoguenov, A; Watson, MG; Tanaka, M; Simpson, C; Cirasuolo, M; Dunlop, J; Peacock, J; Farrah, D; Akiyama, M; Ueda, Y; Smolcic, V; Stewart, G; et al. (2009)
We present the results of a search for galaxy clusters in Subaru-XMM Deep Field. We reach a depth for a total cluster flux in the 0.5-2 keV band of 2x10^{-15} ergs cm^{-2} s^{-1} over one of the widest XMM-Newton contiguous raster surveys, covering an area of 1.3 square degrees. Cluster candidates are identified through a wavelet detection of extended X-ray emission. The red sequence technique allows us to identify 57 cluster candidates. We report on the progress with the cluster spectroscopic follow-up and derive their properties based on the X-ray luminosity and cluster scaling relations. In addition, 3 sources are identified as X-ray counterparts of radio lobes, and in 3 further sources, X-ray counterpart of radio lobes provides a significant fraction of the total flux of the source. In the area covered by NIR data, our identification success rate achieves 86%. We detect a number of radio galaxies within our groups and for a luminosity-limited sample of radio galaxies we compute halo occupation statistics using a marked cluster mass function. We compare the cluster detection statistics in the SXDF with the predictions of concordance cosmology and current knowledge of the X-ray cluster properties, concluding that a reduction of concordance sigma_8 value by 5% is required in order to match the prediction of the model and the data. This conclusion still needs verification through the completion of cluster follow-up.